Evaluation of health experts' education program for becoming multiprofessionals (family health caregiver) regarding health system transformation plan: An application of CIPP model - Tahereh Moghadas-Dastjerdi; Athar Omid; Nikoo Yamani (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND OBJECTIVES: This study was conducted to evaluate the health experts and professionals' education program in order to become multiprofessionals regarding health system transformation plan by a descriptive and educational evaluation method based on the context, input, process, and product (CIPP) evaluation model in 2018. MATERIALS AND METHODS: The statistical population included managers and experts of health deputy (13 people), managers and authorities in health networks (32 people), teachers (251 people), and learners (1914 people). Data were collected by four researcher-made questionnaires based on the CIPP model and evaluation checklist of facilities and equipment. The view of experts was used to measure the face validity and content validity of the questionnaire, and Cronbach's alpha coefficient was used to determine reliability. Data were entered into SPSS 23 software, and data were provided using descriptive statistics (frequency, mean, and standard deviation). RESULTS: The evaluation indicators of the educational course in the field of context were evaluated desirable by province's managers and experts (95% questions), city managers (100% questions), teachers (95% questions), and health caregivers (80% questions). In the field of input, it was evaluated desirable by managers and experts' input of province (60% questions) and city managers (70% questions) and it was evaluated semi-desirable by teachers (78.95% questions) and health caregivers (88.24% questions). In the field of process, it was evaluated desirable by province's managers and experts (73.68% questions) and city managers (66.67% questions) and it was evaluated semi-desirable by teachers (66.67% questions) and health caregivers (94.4% questions). In the field of product, it was evaluated semi-desirable by managers and experts of province (63.63% questions), teachers (81.81% questions), and health caregivers (100% questions) and it was evaluated desirable by city managers (72.72% questions). CONCLUSION: Holding initial service education course of health caregivers has been necessary, and the public health, family, and midwifery disciplines needed to be educated in a university appropriate to the description of tasks of health caregivers.